Step-by-step strategy of electron utilization by binary cocatalysts: Coupling electron-reservoir MoS2 with proton-reduction cobaloxime for enhanced photocatalytic hydrogen evolution - Jianguo He; Lin Chen; Jiahui Yang; Qiongqiong Wang; Hongli Zhang; Keying Lin; Wei Wang; Dong Feng; Baojun Ma (Fuel, 2026)

Synergistic effects of biochar and probiotic fermentation agent on soil aggregate stability, carbon sequestration, and heavy metal(loid)s passivation in paddy fields - Keqi Zhao; Xue Yu; Xifeng Qin; Ruijie Li; Lin Luo; Xiaomei Yang; Liuqin He; Anwei Chen; Jiachao Zhang; Hongli Huang; Xichen Zhao (Agriculture, Ecosystems & Environment, 2026)

Phytolacca acinosa Roxb. induces intestinal toxicity through the histamine–MLCK–tight junction axis: Integrated evidence from proteomics, metabolomics, intestinal organoids and epithelial barrier validation - Yucheng Qi; Xiaoyu Lin; Yangyi Huang; Kou Zhang; Jie Cao; Xiangyue Kong; Xiaobing Cui; Xingde Zhang; Xinzhi Wang; Hao Wu; Hongli Yu (Toxicology Letters, 2026)

Climate-responsive atrium geometry in large public buildings: meta-sample modelling and robust energy-saving ranges across five climates - Zhineng Jin; Hongli Sun; Junkang Song; Wenke Zhong; Zishuang Xia; Hanjie Zheng; Changqi Wen; Bin Xu; Borong Lin (Energy and Buildings, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Strong metal-support interaction boosts the activity and stability of CeO2 supported Pt nanocatalysts for dichloromethane oxidation - Xiuguan Liu; Maosen Xu; Qi Lin; Pengcheng Yu; Yuanhao Ye; Hongli Liu; Deyun Ma (Environmental Research, 2026)

A new mode matching criterion for sectional model wind tunnel flutter test of long-span bridges - Hao Zhang; Ming Li; Zhongyu Lin; Hongli Pang; Xun Liang; Mingshui Li (Engineering Structures, 2026)

Corrigendum to “Calcium isotopic signatures of mid-ocean ridge basalts from the eastern Galápagos Spreading Center that influenced by plume-ridge interaction” [Chemical Geology 715 (2026) 123478] - Yujie Shan; Renqiang Liao; Peijun Lin; Jianghong Deng; Long Du; Xin Li; Hongli Zhu; Zhaofeng Zhang; Weidong Sun (Chemical Geology, 2026)

Divergent impacts of additives on biological risks associated with antibiotic resistance genes during black soldier fly manure composting: A comparative study of biochar, humic acid, and tea residue amendments - Nanyi Wang; Tingzhen Xu; Wenjuan He; Genyi Wu; Xinping Li; Xiaomei Yang; Hongmei Yin; Lin Luo; Lihua Zhang; Liuqin He; Anwei Chen; Man Yu; et al. (Journal of Hazardous Materials, 2026)

Characterization and intrinsic correlations of xylose-cysteine Maillard reaction products across different reaction processes: Insights into reaction degree, functional group variations, antioxidant potential and aroma formation - Hongli Wang; Songyi Lin; Kaiyang Jia; Na Sun; Ruixue Wang; Dong Chen (Food Chemistry, 2026)

Crystalline 2D aromatic polyimine with deep-band for efficient capacitive energy storage - Lichuan Jia; Xiquan Xiao; Zhixing Wang; Wenlong Lin; Mengzhou Liao; Hongli Yang; Ling Xu; Hua-Dong Huang; Shengyang Zhou; Zhong-Ming Li (Chemical Engineering Journal, 2026)

Calcium isotopic signatures of mid-ocean ridge basalts from the eastern Galápagos Spreading Center that influenced by plume-ridge interaction - Yujie Shan; Renqiang Liao; Peijun Lin; Jianghong Deng; Long Du; Xin Li; Hongli Zhu; Zhaofeng Zhang; Weidong Sun (Chemical Geology, 2026)

Dynamic thermal comfort in part-time-local-space heating mode: Interplay effects of localized space heating terminal forms and zonal temperature transitions - Mengfan Duan; Minghao Sun; Shenfei Yu; Hongli Sun; Shenyang Ni; Yifan Wu; Borong Lin; Dongliang Zhao (Energy and Buildings, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Experimental evaluation of the local occupied zone environment in office using a radiation/convection terminal with laminar air supply - Lin Zeng; Nuoa Lei; Hongli Sun; Xingchi Jiang; Enshen Long; Zhu Cheng (Building and Environment, 2026)

Performance of Wetland in Pollutant Removal: a Review - Yifan Zhuo; Sangar Khan; Wenting Liu; Tingting Hu; Yuke Duan; Zongwei Lin; Xinxin Qi; Collins Oduro; Hongli Mu; Naicheng Wu (Water, Air, & Soil Pollution, 2026)

Acicular berthierine-chamosite in coal and lung cancer tissues of Xuan Wei, China - Zheshen Han; Hongli Lin; Renyue Ji; Lijun Liu; Pei Zhang; Chao Jiang; Shijie Zhu; Jialin Xu; Zhenghong Yang; Yunchao Huang; Toshihiro Kogure; Fang Guo; et al. (Journal of Hazardous Materials, 2026)

Comparative analysis of the quality of pan-fried Lentinula edodes with different edible oils: physical, chemical and flavor profiles combined with multivariate statistical analysis - Hongli Wang; Songyi Lin; Xinqian Li; Qinglong Kong; Yuping Tian; Dong Chen (Food Research International, 2025)

Tracing antibiotics in food through dual-mode ratiometric luminescence core-shell nanoparticles - Xin Gao; Qi Li; Hanxiang Wu; Srushti Gadiyaram; Hongli Wen; Abdur Raheem Aleem; Wei Song; Lin Yu; Deshmukh Abdul Hakeem (Food Chemistry, 2025)

A novel Halo Tag-based photo-crosslinking system for efficient drug target identification via chemoproteomic profiling - Xing Liu; Wenjing Ji; Yulin Tao; Yuxiang Gong; Qiannan Zhang; Ruoyao Lin; Yang Yang; Yiting Wang; Shasha Li; Yu Zhang; Hongli Liu; Zhixiang Du; et al. (Analytica Chimica Acta, 2025)

Isolation and characterization of Pseudomonas sp. QX11 with high-efficiency aerobic denitrification for eutrophication control in aquaculture - Shanrui Shen; Yiyi Zhou; Hongli Cheng; Han Qian; Jun Wen; Chunmei Lin; Xiaofang Lai (Science of The Total Environment, 2025)

Strontium diorthovanadate anode for fast-charging lithium-ion battery with low redox potential - Xiaolei Li; Shuangdui Wu; Jian Su; Jing Zhang; Xuguang An; Weitang Yao; Hongli Sun; Borong Lin; Qingquan Kong (Chemical Engineering Journal, 2025)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

Performance adaptability of heating terminals across varying heating loads: From an occupant-centric perspective - Mengfan Duan; Hongli Sun; Yifan Wu; Shenfei Yu; Shuyi Gong; Minghao Sun; Borong Lin; Dongliang Zhao (Building and Environment, 2025)

Neighborhood Energy Supply-Demand Coordinated Design (NES-CoD) in early design stage - Junkang Song; Shuangdui Wu; Zihan Zhang; Hanjie Zheng; Pingan Ni; Shenfei Yu; Songjun Li; Hongli Sun; Borong Lin (Sustainable Cities and Society, 2025)

Evaluation of the temporal and spatial heating performance of different terminals in multiple practical scenarios: From personnel occupancy space perspectives - Mengfan Duan; Hongli Sun; Shenfei Yu; Shuangdui Wu; Shuyi Gong; Yifan Wu; Borong Lin; Dongliang Zhao (Building and Environment, 2025)

Remediation of Heavy Metal Contaminated Soil by Functional Pellets of Charcoal Organic Fertilizer: Rhizosphere and Non-Rhizosphere Soil Microorganisms - Fanghong Li; Xichen Zhao; Renli Qi; Liuqin He; Dan Wan; Jiachao Zhang; Xiaobing Zhang; Ying Wang; Genyi Wu; Hongli Huang; Lin Luo; Lihua Zhang (Water, Air, & Soil Pollution, 2025)

The modulatory effects of shiitake mushrooms on the quality and flavor profiles of steamed low-salt chicken meatballs - Yue Geng; Songyi Lin; Hongli Wang; Yantong Li; Menglong Sheng; Dong Chen (International Journal of Gastronomy and Food Science, 2025)

Enhancing oil/water emulsion separation with inkjet printed beetle-inspired zeolitic imidazolate framework-67 modified membranes - Xinyu Hu; Hongli Xie; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin; Leihong Zhao; Genying Yu (Desalination, 2025)

Organic matter components rather than microbial enzymes and genes predominate CO2/CH4 emissions during composting amended with biochar at different stages - Sijia Gu; Zhanglong Ji; Xuemei Li; Hao Qin; Maosheng Li; Lihua Zhang; Jiachao Zhang; Hongli Huang; Lin Luo (Environmental Pollution, 2025)

Exosome-loaded methacrylated silk fibroin hydrogel delays intervertebral disc degeneration by DKK2-mediated mitochondrial unfolded protein response - Xiao Lu; Zhidi Lin; Liujingzhou Li; Guangyu Xu; Dachuan Li; Zhaoyang Gong; Jiongdong Wu; Tian Gao; Xingyu Guo; Chenpei Xu; Xinlei Xia; Feizhou Lyu; et al. (Chemical Engineering Journal, 2025)

The 14–3–3 gene AaGRF1 positively regulates cold tolerance in kiwifruit - Zhang Zhenzhen; Li Sumei; Sun Shihang; Li Hongli; Zhang Qina; Li Yihang; Li Yukuo; Liu Mingyu; Li Congcong; Sun Leiming; Lin Miaomiao; Qi Xiujuan (Plant Science, 2025)

Retraction notice to “Activities of functional enzymes involved in C, N, and P conversion and their stoichiometry during agricultural waste composting with biochar and biogas residue amendments” [Bioresour. Technol. 345 (2022) 126489] - Nanyi Wang; Liheng Ren; Jiachao Zhang; Mukesh Kumar Awasthi; Binghua Yan; Lihua Zhang; Fachun Wan; Lin Luo; Hongli Huang; Keqi Zhao (Bioresource Technology, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

Effects of biochar and compost on the bioavailability of heavy metals in soil aggregates with varying particle sizes - Fanghong Li; Shilin Jiang; Ge Chen; Dan Wan; Liuqin He; Jiachao Zhang; Keqi Zhao; Hongli Huang; Lin Luo; Genyi Wu; Lihua Zhang (Journal of Soils and Sediments, 2025)

Immobilized Chlorella salina for removing nitrogenous and phosphorous compounds from mariculture tail water - Pengbing Pei; Zijie Xie; Muhammad Aslam; Shuangcheng Jiang; Qi Lin; Hongli Cui; Hong Du (Algal Research, 2025)

Spatial and temporal variation of nutrient distribution in the Yangtze River estuary and adjacent waters: Insights from GOCI data analysis - Chaozhi Yu; Cancan Lu; Yangdong Li; Hongli Li; Jun Lin; Liang Chang (Marine Environmental Research, 2025)

Indoor-outdoor interactive thermal response in public building:onsite data collection and classification through cluster algorithm - Zhineng Jin; Yin zhang; Hongli Sun; Meng Han; Yanhong Zheng; Ying Zhao; Wenyang Han; Menglong Zhang; Bin Xu; Zequn Zhang; Borong Lin (Energy and Buildings, 2025)

Virus susceptibility of a new cell line derived from the muscle of koi (Cyprinus carpio koi) - Hongli Jing; Lin Mei; Jizhou Lv; Min Zhang; Na Wang; Lipu Xu; Shaoqiang Wu (Archives of Virology, 2024)

Mrlac1, an extracellular laccase, is required for conidial morphogenesis as well as the well adaptability in field of Metarhizium rileyi - Yunlong Lin; Liqin Fan; Xi Gao; Xiaoli Li; Miao Lin; Qi Luo; Hongli Li; Zhongkang Wang; Guoxing Wu (Pesticide Biochemistry and Physiology, 2024)

Differential impacts of small hydropower plants on macroinvertebrate communities upstream and downstream under ecological flow - Zongwei Lin; Xinxin Qi; Mali Li; Yuke Duan; Huimin Gao; Guohao Liu; Sangar Khan; Hongli Mu; Qinghua Cai; Beata Messyasz; Naicheng Wu (Journal of Environmental Management, 2024)

Small hydropower plants affect aquatic community diversity: A longitudinal study under ecological flow - Xinxin Qi; Zongwei Lin; Huimin Gao; Mali Li; Yuke Duan; Guohao Liu; Sangar Khan; Hongli Mu; Beata Messyasz; Naicheng Wu (Journal of Environmental Management, 2024)

Gradient doping–induced triphasic intergrowth hexacyanoferrate cathode for high-performance sodium-ion batteries - Lin Xu; Ming Chen; Guohu Chen; Hongli Wu; Wenwei Wu; Xuehang Wu (Chemical Engineering Journal, 2024)

Development and validation of sloped ground pressure prediction model for a tracked tractor in hilly and mountainous environments - Fuzeng Yang; Qi Liu; Yuxuan JI; Hongli Chu; Luojia Duan; Zhong Lin; Yuanfeng Shou; Zhijie Liu (Soil and Tillage Research, 2024)

Insight into mitigation mechanisms of N2O emission by biochar during agricultural waste composting - Jun Liu; Yunlong Hu; Sijia Gu; Xuemei Li; Zhanglong Ji; Hao Qin; Lihua Zhang; Jiachao Zhang; Hongli Huang; Binghua Yan; Lin Luo (Bioresource Technology, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Global quantification of emerging and legacy per- and polyfluoroalkyl substances in indoor dust: Levels, profiles and human exposure - Hongli Tan; Shuqin Tang; Liu Yang; Jing Li; Yongfeng Deng; Hao Shen; Qingyuan Dai; Yifei Gao; Pengfei Wu; Lin Zhu; Zongwei Cai (Science of The Total Environment, 2024)

Purification, characterisation and visualisation of soybean protein hydrolysis by aspergillopepsin I from mangrove Aspergillus tubingensis - Hongli Yao; Shuangping Liu; Rui Chang; Tiantian Liu; Dongna Ma; Xiao Han; Congyu Lin; Zhilei Zhou; Jian Mao (International Biodeterioration & Biodegradation, 2024)

Occupant-centric dynamic heating demand in residential buildings based on a temporal-spatial combined quantification method - Mengfan Duan; Hongli Sun; Yifan Wu; Shuangdui Wu; Borong Lin; Dongliang Zhao; Wenxing Shi; Hecheng Yang (Building and Environment, 2024)

Highly water-soluble and biocompatible hyaluronic acid functionalized upconversion nanoparticles as ratiometric nanoprobes for label-free detection of nitrofuran and doxorubicin - Abdur Raheem Aleem; Rihui Chen; Tonghua Wan; Wei Song; Chuyan Wu; Xue Qiu; Qiuqiang Zhan; Kuncheng Xu; Xin Gao; Tianci Dong; Xiang Chen; Lin Yu; et al. (Food Chemistry, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

FvDFR2 rather than FvDFR1 play key roles for anthocyanin synthesis in strawberry petioles - Xinyu Li; Xi Luo; Zhongchi Liu; Chong Wang; Anqi Lin; Kun Xiao; Minghao Cao; Junmiao Fan; Hongli Lian; Pengbo Xu (Plant Science, 2024)

Construction land reduction projects as a pathway to sustainability: an empirical analysis of risks factors in China - Bingxu Mu; Yuming Zhu; Naveed Ahmad; Jiahe Zhou; Lei He; Hongli Lin (Environmental Science and Pollution Research, 2024)

Phthalate metabolites in breast milk from mothers in Southern China: Occurrence, temporal trends, daily intake, and risk assessment - Yangyang Liu; Minhua Xiao; Kaiqin Huang; Juntao Cui; Hongli Liu; Yingxin Yu; Shengtao Ma; Xihong Liu; Meiqing Lin (Journal of Hazardous Materials, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Atomic-level surface modification of ultrathin Bi2WO6 nanosheets for boosting photocatalytic CO2 reduction - Lulu Zhao; Huilin Hou; Lin Wang; Chris R. Bowen; Jinguo Wang; Ruifang Yan; Xiaoqiang Zhan; Hongli Yang; Man Yang; Weiyou Yang (Chemical Engineering Journal, 2024)

A quantitative study on the characteristics of desiccation cracks and their effect on the shear failure characteristics of granite red soil - Yue Zhang; Yimin Huang; Zumei Wang; Menglu Shi; Jinshi Lin; Fangshi Jiang; Hongli Ge; Yanhe Huang (Bulletin of Engineering Geology and the Environment, 2024)

Multiply-mesoporous hydrophilic titanium dioxide nanohybrid for the highly-performed enrichment of N-glycopeptides from human serum - Yunfan Lin; Chengrun Du; Hongmei Ying; Yifan Zhou; Fangfang Kong; Hongli Zhao; Minbo Lan (Analytica Chimica Acta, 2024)

A polylactide based multifunctional hydrophobic film for tracking evaluation and maintaining beef freshness by an electrospinning technique - Xinxin Liu; Xiushuang Song; Dejiao Gou; Hongli Li; Lin Jiang; Minglong Yuan; Mingwei Yuan (Food Chemistry, 2023)

Relative contribution of ammonia-oxidizing bacteria and denitrifying fungi to N2O production during rice straw composting with biochar and biogas residue amendments - Xu Lin; Naif Abdullah Al-Dhabi; Fanghong Li; Nanyi Wang; Hua Peng; Anwei Chen; Genyi Wu; Jiachao Zhang; Lihua Zhang; Hongli Huang; Binghua Yan; Lin Luo; et al. (Bioresource Technology, 2023)

Multifunctional regulation of NADPH oxidase in growth, microsclerotia formation and virulence in Metarhizium rileyi - Liqin Fan; Bingjie Li; Jiahui Wang; Xinxin Li; Feilong Ma; Fang Du; Hongli Li; Yunlong Lin (Biotechnology Letters, 2023)

Super-strong Zn and S atomic terminals in an organic/inorganic hybrid S-scheme polyimide based heterojunction for efficient photocatalytic treatment of mixed pollutant wastewater - Siyi Li; Yushu Wang; Hongli An; Junjun Lin; Shuang Jiang; Tianyong Zhang; Bin Li (Chemical Engineering Journal, 2023)

Dynamic process simulation of indoor temperature distribution in radiant-convective heating terminals - Yifan Wu; Hongli Sun; Zixu Yang; Mengfan Duan; Borong Lin; Hengxin Zhao (Building and Environment, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Potential ecological risks of heavy metals and Cd accumulation characteristics of Suaeda salsa under different Cd input and water logging conditions in the Yellow River estuary, China - Hongli Song; Lin Kuang; Lizhi Wang; Wanni Yu; Yuanzhi Wu; Juan An; Xiyuan Wu (Environmental Science and Pollution Research, 2023)

Understanding stakeholder relationships in sustainable brownfield regeneration: a combined FAHP and SNA approach - Hongli Lin; Yuming Zhu; Jiahe Zhou; Bingxu Mu; Caihong Liu (Environment, Development and Sustainability, 2023)

Response characteristics of antibiotic resistance genes and bacterial communities during agricultural waste composting: Focusing on biogas residue combined with biochar amendments - Yuewei He; Xiaowei Yin; Fanghong Li; Bo Wu; Ling Zhu; Dabing Ge; Nanyi Wang; Anwei Chen; Lihua Zhang; Binghua Yan; Hongli Huang; Lin Luo; et al. (Bioresource Technology, 2023)

Analysis of thermal comfort experience using peak-end rule with air conditioner in heating season - Zixu Yang; Mengdi Cui; Hansong Xiao; Hongli Sun; Baolong Wang; Borong Lin; Wenxing Shi (Building and Environment, 2023)

Modeling Secondary Organic Aerosols in China: State of the Art and Perspectives - Jingyi Li; Haowen Zhang; Lin Li; Fei Ye; Hongli Wang; Song Guo; Na Zhang; Momei Qin; Jianlin Hu (Current Pollution Reports, 2023)

Sharply and simultaneously increasing pollutant accumulations in cells of organisms induced by rare earth elements in the environment of Nanjing - Qing Yang; Mengzhu Cheng; Qing Zhou; Lihong Wang; Yunlong Jiao; Yongqiang Liu; Shuya Zhang; Li Tan; Zhenhong Gu; Hong Zhu; Hongli Luo; Daozhe Lin; et al. (Chemosphere, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Effects of Biocontrol Agents Application on Soil Bacterial Community and the Quality of Tobacco - Zhongkui Li; Yulan Chen; Aifen Ling; Hongli Li; Zhengquan Lin; Yan Wang (Current Microbiology, 2022)

Proteomic differences between Vibrio tubiashii strains with high- or low-virulence levels isolated from diseased ivory snail Babylonia areolata - Ruixuan Wang; Xiaojing Liu; Jiangyong Wang; Huizhu; Xiaozhi Lin; Jingfeng Sun; Hongli Mou; Ting Zhang; Xilan Ma (Aquaculture International, 2022)

Efficient removal of pefloxacin from aqueous solution by acid–alkali modified sludge-based biochar: adsorption kinetics, isotherm, thermodynamics, and mechanism - Hongli Huang; Yongxin Zheng; Dongning Wei; Guang Yang; Xin Peng; Lingjia Fan; Lin Luo; Yaoyu Zhou (Environmental Science and Pollution Research, 2022)

Estimating the Baseline Error of Wide-Swath Altimeters Using Nadir Altimeters via Numerical Simulation - Xiangying Miao; Yongjun Jia; Mingsen Lin; Hongli Miao (Journal of Ocean University of China, 2022)

Microplastics in Mollusks: Research Progress, Current Contamination Status, Analysis Approaches, and Future Perspectives - Ruixuan Wang; Hongli Mou; Xiaozhi Lin; Hui Zhu; Bing Li; Jiangyong Wang; Muhammad Junaid; Jun Wang (Frontiers in Marine Science, 2021)
Plastic fragments < 5 mm, known as microplastics (MPs), are ubiquitously present in the marine environment. Research on MPs pollution has gradually shifted from field investigations to laboratory studies. With the rapid growth of plastic consumption and the prevalence of aquaculture products, studies on marine MPs have focused on key marine species, such as mollusks. This review summarizes the recent knowledge including 77 important relevant literatures (from 2010 to 2021) on MPs contamination in mollusks with the objectives of (1) elucidating the current status of MPs pollution levels in mollusks, (2) highlighting the main methods and techniques for separation, extraction, and identification of MPs in soft tissues of bivalves and (3) presenting the current research progress and future directions. The review visually presents some of the important results in graphic form, which shows that the most common polymer plastics in bivalves are polypropylene, polystyrene, and polyethylene, and the shapes were mainly fiber and threadiness, mollusks are more likely to feed smaller MPs, most of the MPs in bivalves are less than 500 μm, and the abundance of MPs in seawater and the abundance of MPs in mollusks have a positive relationship, etc. This review will provide a comprehensive reference for studies of microplastics in marine organisms and the ecological pollution, and also has scientific guiding significance in the research method.

Differential proteomics reveals main determinants for the improved pectinase activity in UV-mutagenized Aspergillus niger strain - Weiling Lin; Xiaohong Xu; Ruirui Lv; Wei Huang; Hafeez ul Haq; Yuanyuan Gao; Hongli Ren; Canhua Lan; Baoyu Tian (Biotechnology Letters, 2021)

Trace and rare-earth element characteristics of fine-grained sediments in the Upper Triassic Xujiahe Formation in the western Sichuan Basin, SW China: implications for the provenance and depositional environment - Yu Yu; Liangbiao Lin; Hongli Nan (Carbonates and Evaporites, 2021)

Differences in Soil Microbial Community Composition Between Suppressive and Root Rot-Conducive in Tobacco Fields - Yaru Ding; Yulan Chen; Zhengquan Lin; Yangyang Tuo; Hongli Li; Yan Wang (Current Microbiology, 2021)

Effect of Manure Compost on Distribution of Cu and Zn in Rhizosphere Soil and Heavy Metal Accumulation by Brassica juncea - Hongli Huang; Lin Luo; Liuhui Huang; Jiachao Zhang; Petros Gikas; Yaoyu Zhou (Water, Air, & Soil Pollution, 2020)

Stakeholders’ perspective on strategies to promote contaminated site remediation and brownfield redevelopment in developing countries: empirical evidence from Pakistan - Naveed Ahmad; Yuming Zhu; Jing Shao; Hongli Lin (Environmental Science and Pollution Research, 2020)

Development of polyclonal-antibody-coated immunomagnetic beads for separation and detection of koi herpesvirus in large-volume samples - Min Zhang; Yingying Li; Hongli Jing; Na Wang; Shaoqiang Wu; Qing Wang; Xiangmei Lin (Archives of Virology, 2020)

Correlation between shear strength and soil physicochemical properties of different weathering profiles of the non-eroded and collapsing gully soils in southern China - Bifei Huang; Ming Qiu; Jinshi Lin; Jialin Chen; Fangshi Jiang; Ming-kuang Wang; Hongli Ge; Yanhe Huang (Journal of Soils and Sediments, 2019)

Expression patterns of alpha-amylase and beta-amylase genes provide insights into the molecular mechanisms underlying the responses of tea plants (Camellia sinensis) to stress and postharvest processing treatments - Chuan Yue; Hongli Cao; Hongzheng Lin; Juan Hu; Yijun Ye; Jiamin Li; Zhilong Hao; Xinyuan Hao; Yun Sun; Yajun Yang; Xinchao Wang (Planta, 2019)

A scientometric analysis and visualization of global research on brownfields - Hongli Lin; Yuming Zhu; Naveed Ahmad; Qingye Han (Environmental Science and Pollution Research, 2019)

Characterization and application of monoclonal antibodies against channel catfish virus (CCV) - Hongli Jing; Min Zhang; Shaoqiang Wu; Xiangmei Lin; Longying Gao; Na Wang (Archives of Virology, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Influences of meteorological conditions on interannual variations of particulate matter pollution during winter in the Beijing–Tianjin–Hebei area - Jianjun He; Sunling Gong; Hongli Liu; Xingqin An; Ye Yu; Suping Zhao; Lin Wu; Congbo Song; Chunhong Zhou; Jie Wang; Chengmei Yin; Lijuan Yu (Journal of Meteorological Research, 2017)

Nonparametric estimations of the sea state bias for a radar altimeter - Hongli Miao; Yujie Jing; Yongjun Jia; Mingsen Lin; Guoshou Zhang; Guizhong Wang (Acta Oceanologica Sinica, 2017)

Establishment and characterization of a heart-derived cell line from goldfish (Carassius auratus) - Hongli Jing; Xiangmei Lin; Lipu Xu; Longying Gao; Min Zhang; Na Wang; Shaoqiang Wu (Fish Physiology and Biochemistry, 2017)

Establishment from the snout and kidney of goldfish, Carassius auratus, of two new cell lines and their susceptibility to infectious pancreatic necrosis virus - Hongli Jing; Longying Gao; Min Zhang; Na Wang; Xiangmei Lin; Lifeng Zhang; Shaoqiang Wu (Fish Physiology and Biochemistry, 2016)

Detection of grass carp reovirus (GCRV) with monoclonal antibodies - Jing Hongli; Zhang Lifeng; Fang Zhenzhen; Xu Lipu; Zhang Min; Wang Na; Jiang Yulin; Lin Xiangmei (Archives of Virology, 2014)

A loop-mediated isothermal amplification method for the detection of members of the genus Ranavirus - Zhang Min; Jing Hongli; Zhang Lifeng; Wang Na; Wu Shaoqiang; Lin Xiangmei (Archives of Virology, 2013)

Effects of sediment burial disturbance on seedling survival and growth of Suaeda salsa in the tidal wetland of the Yellow River estuary - Zhigao Sun; Xiaojie Mou; Guanghui Lin; Lingling Wang; Hongli Song; Huanhuan Jiang (Plant and Soil, 2010)